Pengaruh Perputaran Modal Kerja, Likuiditas, Leverage Dan Perputaran Total Aset Terhadap Profitabilitas Dengan Ukuran Perusahaan Sebagai Variabel Moderating - Pitri Afriani; Liza Novietta; Azwansyah Habibie (LPPM STIKes SITI HAJAR dan Insight Power, 2022)
This research was conducted with the aim of knowing the effect of working capital turnover, liquidity, leverage and total asset turnover on profitability with firm size as the moderating variable. This type of research is quantitative research with a causal approach. The population used in this study are food and beverage companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020 and there are 13 companies that are taken so that a total sample of 65. The sampling technique uses the purposive sampling method. The analysis method of this research uses multiple linear regression and Moderated Regression Analysis. The results show that liquidity and leverage have a significant effect on profitability, while working capital turnover and total asset turnover have no significant effect on profitability, and firm size can moderate the relationship between liquidity and profitability. Company size does not moderate the relationship between working capital turnover, leverage and total asset turnover on profitability in food and beverage companies listed on the Indonesia Stock Exchange (IDX) in 2016-2022.Keywords: Working Capital Turnover, Liquidity, Leverage, Total Asset Turnover, Company Size, and Profitability